Ethical Awareness among Undergraduate Nursing Students of Khyber Pukhtankhwa - Haseen Jamal, Shabana, Shakirullah, Sheraz Khan, Amir Sultan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify the academic ethical awareness among the undergraduate nursing students of Khyber Pukhtankhwa Pakistan. Methodology: The study was conducted in October – November 2022 in Nursing Institutes of Khyber Pukhtankhwa while using descriptive cross-sectional design through purposive sampling technique. The data was collected through valid and reliable questionnaire having chronbach of 0.95. Data was analyzed through Microsoft excel and SPSS 20 after ethical approved by institutional review board. Results: The ethical awareness mean score of male students were 2.4±0.91 higher than female students 2.01±0.76. Furthermore the mean score of 7th semester students were higher 2.7±0.91 than other semester students. The overall means score regarding ethical awareness among nursing students was 2.32±0.89. Conclusion: Study concludes that the level of awareness improves with advancement to next semesters and is significantly associated with gender, age and semester. Implications: The findings will help the nursing educators to assess the current ethical practices of undergraduate nursing students and to improve further the academic and clinical ethical practices among nursing students. Keywords: Undergraduate nursing students, academic ethics, ethical practices